please solve in notebook ...
Attachments:
![](https://hi-static.z-dn.net/files/da6/c9fa46e4b80d86ce28be017c44beac7a.jpg)
Answers
Answered by
2
Determinant =
![1( \: (1)(1) - ( {x}^{2} x )) - x( {x}^{2} - {x}^{2} ) + {x}^{2} ( {x}^{4} - x) 1( \: (1)(1) - ( {x}^{2} x )) - x( {x}^{2} - {x}^{2} ) + {x}^{2} ( {x}^{4} - x)](https://tex.z-dn.net/?f=1%28+%5C%3A+%281%29%281%29+-+%28+%7Bx%7D%5E%7B2%7D+x+%29%29+-+x%28+%7Bx%7D%5E%7B2%7D++-++%7Bx%7D%5E%7B2%7D+%29+%2B++%7Bx%7D%5E%7B2%7D+%28+%7Bx%7D%5E%7B4%7D++-+x%29)
![= (1 - {x}^{3} ) + {x}^{3} ( {x}^{3} - 1) = (1 - {x}^{3} ) + {x}^{3} ( {x}^{3} - 1)](https://tex.z-dn.net/?f=+%3D+%281+-++%7Bx%7D%5E%7B3%7D+%29+%2B++%7Bx%7D%5E%7B3%7D+%28+%7Bx%7D%5E%7B3%7D++-+1%29)
![= (1 - {x}^{3} )^{2} = (1 - {x}^{3} )^{2}](https://tex.z-dn.net/?f=+%3D+%281+-++%7Bx%7D%5E%7B3%7D+%29%5E%7B2%7D+)
khushu18:
thankuu ... bt without expanding
Answered by
1
we can apply different row nd colum transformation
Attachments:
![](https://hi-static.z-dn.net/files/db1/675bfefe104281f62414fbedd2d7f9c7.jpg)
Similar questions